CORRELATION OF THE ENGLISH FAIRY TALE'S PLOT STRUCTURE AND ITS PROSODIC ORGANISATION - Larysa Taranenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
In the paper on the basis of a systemic analysis of the English fairy tales' semantic, functional and structural characteristics the author updates its definition of a small form folk text, outlines typical genre characteristics and substantiates a hierarchical subordination of its functional features. The paper also advances the algorithmic model, representing the steps of unfolding the English fairy tales' plot elements, which serves as a theoretical and methodological ground for the experimental phonetic study of prosodic means that organise the text of a fairy tale. Within the process of model formation, the author performs a matrix analysis of the fairy tale's content and compositional structure, presented as a systemic algorithmic scheme. The evaluation of emotional and pragmatic potentials of the spoken fairy tale made it possible to describe the peculiarities of prosodic features functioning within its structural elements (exposition → development of the events → climax → denouement) and at their junctures as well as substantiate its invariant and variant intonation patterns. The carried out auditory analysis proves that there is a direct correlation between the fairy tale's plot structure and its prosodic means, whose specific interaction triggers creative and cognitive processes in the recipient's mind aimed at conveying the text pragmatic aim.